Developing an Android-based bilingual e-glossary application of English for Specific Purposes (ESP) - Siti Rohani; Achmad Suyono (English Language Teaching Educational Journal, 2021)
One effort considered quite effective in assisting vocabulary mastery and facilitating understanding of English texts is the provision of a bilingual glossary (English-Indonesian). This glossary becomes more essential especially for non-English Department students because basically English for Specific Purposes has a higher level of difficulty than general English. This study was a design and development research, with a product cluster and research tool. There were four main stages undergone, namely preliminary study, product development, expert validation, and field-testing. The research subjects were students and lecturers in seven departments of both commerce and engineering schools at State Polytechnic of Malang. Instruments of data collection used were questionnaires, interviews, and focused group discussion. The output of the study is an android application of bilingual E-Glossary of English for Specific Purposes. There were seven fields of glossary, each of which consists of vocabulary in English, the translation or description in Indonesian language, along with example sentences in two languages. Pictures are also displayed for easy understanding of the vocabulary. Field testing proves that the E-Glossary application is quite effective in helping users in comprehending English texts better. The application is also considered attractive, easy to use, and easy to understand.